Vinflunine in the treatment of advanced urothelial cancer: clinical evidence and experience. (January 2017) - Gerullis, Holger; Wawroschek, Friedhelm; Köhne, Claus-Henning; Ecke, Thorsten Holger
Vinflunine (VFL) has been approved in Europe for second-line treatment of metastatic and advanced urothelial cancer after failure of platin-containing therapy. Since approval, the drug has been investigated in few clinical trials. Most of the currently available reports describe experiences with VFL in a daily clinical setting. This review gives a short overview on clinical experiences and clinical trials involving VFL since the approval of this drug in 2009.